Therapeutic Efficacy of CD34-Derived Allogeneic Dendritic Cells Engineered to Express CD93, CD40L, and CXCL13 in Humanized Mouse Models of Pancreatic Cancer - Sara Huerta-Yepez; Jose D. Gonzalez; Neha Sheik; Senay Beraki; Elango Kathirvel; Ariel Rodriguez-Frandsen; Po-Chun Chen; Tiran Sargsyan; Saleemulla Mahammad; Mark R. Dybul; Lu Chen; Francois Binette; et al. (Vaccines)
Background/Objectives: Pancreatic cancer remains the fourth leading cause of cancer-related deaths. While peripheral blood-derived mature dendritic cell (mDC) vaccines have shown potential in eliciting anti-tumor immune responses, clinical efficacy has been limited. This study aimed to enhance the potency and scalability of DC-based immunotherapy by developing an allogeneic DC platform derived from CD34+ hematopoietic stem cells (HSCs), genetically engineered to overexpress CD93, CD40L, and CXCL13, followed by maturation and tumor antigen pulsing. Methods: Engineered DCs were generated from CD34+ HSCs and matured in vitro after lentiviral transduction of CD93, CD40L, and CXCL13. Tumor lysates were used for antigen pulsing. A scrambled-sequence control DC was used for comparison. In vitro assays were performed to assess T cell activation and tumor cell killing. In vivo efficacy was evaluated using orthotopic pancreatic tumors in BLT and PBMC-humanized NSG mice established with the MiaPaca-2 (MP2) cell line. Results: Engineered DCs significantly enhanced T cell activation and tumor-specific cytotoxicity in vitro compared to control DCs. Antigen pulsing further amplified immune activation. In vivo, treated humanized mice showed increased CD4+, CD8+, and NK cell frequencies in peripheral blood and within tumors, correlating with reduced tumor burden. Conclusions: Our data shows that the antigen-pulsed, engineered DCs have the potency to activate immune cells, which leads to a significant reduction in pancreatic tumors and therefore could potentially provide an effective therapeutic opportunity for the treatment of pancreatic cancer and other solid tumors.